Ximelagatran for the secondary prevention of venous thromboembolism - Schulman, Sam; Lundström, Torbjörn; Wåhlander, Karin; Billing Clason, Solveig; Eriksson, Henry; for the THRIVE III Investigators (Thrombosis and Haemostasis, 2005)
In the randomized, double-blind THRIVE III trial, the oral direct thrombin inhibitor ximelagatran (24 mg twice daily) significantly reduced the incidence of recurrent venous thromboembolism (VTE) versus placebo over 18 months or until premature study drug discontinuation. A complementary follow-up analysis (intention-to-treat) was conducted post-study to evaluate the cumulative risks of locally-confirmed recurrent VTE and death (Kaplan-Meier procedure) over the full 18-month study period, regardless of whether patients discontinued study drug prematurely. Hazard ratios (HRs) between treatments were estimated using Cox proportional hazard modeling. Of 612 and 611 patients receiving ximelagatran and placebo, respectively, 149 and 181 discontinued treatment prematurely. Of these discontinuations, further information could not be collected for 14 and 13patients in the ximelagatran and placebo groups, respectively; among the remaining patients, four VTE events and four deaths occurred in the ximelagatran group, and oneVTE event and five deaths occurred in the placebo group. The resulting cumulative risks of VTE (3.2% vs. 12.7%; HR 0.21; 95% confidence interval [CI], 0.12, 0.36;P < 0.0001) and pulmonary embolism (0.8% vs. 5.2%; HR 0.13; 95% CI 0.04, 0.36;P < 0.0001) were significantly lower in the ximelagatran than in the placebo group over 18 months. Death from any cause over 18 months occurred in 10 and 12 patients, respectively (HR 0.83;95% CI 0.36,1.93;P = 0.7). This complementary follow-up analysis confirms the benefit of oral ximelagatran 24 mg twice daily, administered without coagulation monitoring or dose adjustment, for the long-term secondary prevention of VTE.
Keywords: Oral direct thrombin inhibitor; secondary prevention; THRIVE III; venous thromboembolism; ximelagatran